Pengaruh Kesadaran Merek Dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Pada Peacock Coffee Di Jalan Gajah Mada Semarang) - A, Besta Aditya; Pradhanawati, Ari (Jurnal Ilmu Administrasi Bisnis, 2017)
Purchasing decision stage decision process where the consumer actually purchases theproduct. Generated by the purchasing decisions of consumers would be more difficult, especially in acompetitive market because there are many options that make the consumer is free to make his choice.Allegations of factors that influence the purchase decision is brand awareness and quality of service.This study was conducted to determine the effect of brand awareness and quality of service onpurchasing decisions in Peacock Coffee Gajah Mada Semarang. In this study using the technique ofsampling non probability sampling with accidental sampling that can be taken 155 consumerrespondents Peacock Coffee Gajah Mada Semarang. The data analysis used is regression. The resultsshowed that the results of the t 19.591> t table 1.975 then kesdaran brand (X1) has a positive andsignificant impact on purchasing decisions (Y), the results of the t 21.302> t table 1.975, the qualityof service (X2) has a positive and significant impact on the purchasing decisions (Y). The resultsshowed that there was a positive and significant influence between brand awareness and servicequality together to purchasing decision.